Numerical study of energy dissipation and block barriers in stepped spillways - Mehdi Karami Moghadam (IWA Publishing, 2021)
In this research, the accuracy of the Flow-3D numerical model in the flow simulation in a stepped spillway was probed using data obtained from the physical model. In addition, the effects of block barriers on the energy dissipation rate were investigated. To adopt a proper turbulent model, Renormalization Group k-ε, RNG k-ε, and standard k-ε models were employed. Then, the Flow-3D was run in five discharges for nine spillways with the ratios of block length to step length (Lb/l) and block height to step height (Hb/h) as 0.3, 0.4, and 0.5. The results indicated that both turbulent models had almost similar outcomes though the run time of the RNG k-ε model was shorter. The blocks with a shorter length in low ratios of Hb/h and the lengthier blocks in high ratios of Hb/h undergo more relative energy dissipation relative to the no-block situation. For Hb/h = 0.3 and Lb/l equal to 0.3, 0.4, and 0.5, the relative energy dissipation climbed on average as 8.5, 6.5, and 4.5% respectively, compared with the no-block case. The most influence exerted on relative energy dissipation was obtained via the blocks with Hb/h = Lb/l equal to 0.3 and 0.5 with respective increases of 8.6 and 8.4%. HIGHLIGHTS The Flow-3D model applied to examine the effects of height and length of the block on the energy dissipation.; As the discharge increases, the energy dissipation decreases and the effects of blocks increases.; Shorter blocks at lower elevations and longer blocks at higher length had the highest energy dissipation.; The blocks with length/height equal to 0.3 and 0.5 were assigned the most increase in energy dissipation.;